Self-Tuning Multi-Transmitter Wireless Power Transfer to Freely Positioned Receivers - Xiaojie Dang; Prasad Jayathurathnage; Sergei A. Tretyakov; Constantin R. Simovski (IEEE Access, 2020)
Free positioning of receivers is one of the key requirements for many wireless power transfer (WPT) applications, necessary from the end-user point of view. However, realization of stable and effective wireless power transfer for freely positioned receivers is technically challenging because of the need of complex control and tuning circuits. In this paper, we propose a concept of power channeling via an array of repeaters that enables self-tuning of multi-transmitter WPT systems without any sensing or control elements. The proposed WPT system consists of uncoupled transmitters and uncoupled repeaters which form independent power transfer channels. The proposed self-tuning WPT system is capable of maintaining stable output power with constant high efficiency regardless of the receiver position. Namely, our numerical and experimental results for a four-transmitter WPT system in form of a linear array show the efficiency 94.5 ± 2% for any position of the receiver within 20 mm range.